Action Research in Action: From University to School Classrooms. (11th July 2012) - Miskovic, Maja; Efron, Efrat Sara; Ravid, Ruth
Abstract : This multiyear mixed-method study was conducted to understand (a) the perceptions of the preservice and in-service teachers regarding the significance of action research in their teaching career and (b) how teachers draw on skills developed in the research courses as they initiate a reflective inquiry and conduct research in their own classrooms. Based on 176 surveys, we conclude that research plays an important role in the teachers' professional life and that teachers desire (a) to have more time to do research, and (b) collaboration with and assistance from colleagues and administrators. Ethnographic data from three participants revealed that each understood research differently, which affected what was unfolding in the classrooms. Implications for teacher research are discussed.